One and a Half Syndrome and Internuclear Ophthalmoplegia as Neuro-Ophthalmological Manifestations in Patients with Brainstem Stroke: A Case Series - Mahardhika Maghfirani Sadewa; Celine Cornelia; Maula Nuruddin Gaharu; Hamdani, Ismi Adhanisa (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Brainstem stroke syndrome accounts for 10-15% of all types of strokes, which may result in relatively rare neuroophthalmological manifestations. The aim of this case report is to report findings of one and a half syndrome (OAHS) and internuclear ophthalmoplegia in a patient with brainstem stroke. Case presentation: First case, female, 56 years old, came with sudden weakness on the right side of the body. One and a half syndrome was found, namely when asked to glance to the left, conjugate gaze palsy was obtained horizontally, and when asked to glance to the right, there was adduction inability of the left eye (ipsilateral). Right eye abduction was normal with present nystagmus. Paresis of right central CN. VII, XII was present, along with hemiparesis dextra (contralateral). Head CT scan shows hemorrhage in pons and intraventricular. Second case, female, 65 years old, came with a protruding mouth, vertigo, and sudden double vision Internuclear ophthalmoplegia was present, namely an adduction inability of the left eye (ipsilateral) when asked to glance to the right. Right eye abduction was normal with present nystagmus. no abnormalities were seen in the primary position and when asked to glance to the left. Paresis of right peripheral CN. VII, hemiparesis and right (contralateral) hemihypesthesia was present. MRI shows multiple chronic infarcts as well as subacute infarcts in bilateral parietal and pons. Conclusion: Clinical knowledge is necessary for topic determination, rehabilitation process and evaluation.